1994
DOI: 10.1073/pnas.91.7.2839
|View full text |Cite
|
Sign up to set email alerts
|

Fatal familial insomnia and familial Creutzfeldt-Jakob disease: different prion proteins determined by a DNA polymorphism.

Abstract: Fatal familial insomnia and a subtype of Creutzfeldt-Jakob disease, two clinicaly and pathologically distinct dies, are linked to the same mutation at codon 178 (Asp-178 --Asn) but segregate with different genotypes de-termined by this mutation and the methionivaline polymorphism at codon 129 of the prion protein gene. The abnormal isoforms of the prion protein in these two diseases were found to differ both in the relative abundance of glycosylated forms and in the size of the protease-restant fagments. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
158
0
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(165 citation statements)
references
References 29 publications
4
158
0
3
Order By: Relevance
“…17,19,29,44 Yull et al 35 found that the type 1-like band detected by 12B2 in vCJD maintained the very characteristic glycoform ratio of PrP Sc type 2B and concluded that the band they considered a PrP Sc resistant core could not be a common type 1. We consider this result, which was also reproduced by us, as further evidence that the type 1-like band recognized by 12B2 in vCJD cases represents partially cleaved fragments of PrP Sc type 2B rather than real, bona fide PrP Sc type 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,19,29,44 Yull et al 35 found that the type 1-like band detected by 12B2 in vCJD maintained the very characteristic glycoform ratio of PrP Sc type 2B and concluded that the band they considered a PrP Sc resistant core could not be a common type 1. We consider this result, which was also reproduced by us, as further evidence that the type 1-like band recognized by 12B2 in vCJD cases represents partially cleaved fragments of PrP Sc type 2B rather than real, bona fide PrP Sc type 1.…”
Section: Discussionmentioning
confidence: 99%
“…Although uncertainties remain on the molecular basis of TSE strains and the relationship between strains and PrP, several lines of evidence indicate that PrP Sc exists in a variety of molecular subtypes showing distinctive physicochemical properties 13,[17][18][19][20][21][22][23][24][25] (for reviews about more recent studies see Parchi et al 26 and Baron et al 27 ). Most significantly, PrP Sc molecules derived from different strains or disease variants with distinct pathology often vary in their N-terminal site of PK cleavage.…”
mentioning
confidence: 99%
“…Although sCJD is rare, with an incidence of 0.6-1.2 per million, it accounts for about 85% of all recognized human cases of prion disease (Brandel et al, 2000;Hill et al, 2003). Two predominant PrP sc types have been identified, based on the gel mobility of the PrP sc fragments resistant to proteinase K (PK) treatment, and they are associated with different CJD phenotypes (Cali et al, 2006;Gambetti et al, 2003;Monari et al, 1994;Petersen et al, 1994). Parallel to this, PRNP polymorphism at codon 129 (Met 129 →Val) modulates sensitivity to CJD, and methionine homozygosis is a risk factor for sporadic and variant CJD (Collinge, 1999;Ladogana et al, 2005;Palmer et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Persuasive evidence that strain-specific information is enciphered in the tertiary structure of PrP Sc comes from transmission of two different inherited human prion diseases to mice expressing a chimeric MHu2M PrP transgene (27). In FFI, the protease-resistant fragment of PrP Sc after deglycosylation has a mass of 19 kDa, whereas in fCJD(E200K) and most sporadic prion diseases it is 21 kDa (Table 6) (273,274). This difference in molecular size was shown to be due to different sites of proteolytic cleavage at the NH 2 termini of the two human PrP Sc molecules reflecting different tertiary structures (273).…”
mentioning
confidence: 99%